Subjecffve effects of cannabidiol in anxiety disorder and canabinoid excretion in chronic daily cannabis smokers during sustained abstinence - Bergamaschi, Mateus Machado (2012)
This dissertation is divided into three parts. The first part aimed to investigate the cannabidiol anxiolytic effect in treatment-naïve individuals with social anxiety disorder through simulation of public speaking. Twenty-four never-treated social anxiety disorder subjects were allocated to receive 0 or 600 mg cannabidiol (CBD; n=12) in a double-blind randomized design. The same number of controls performed the simulation of a public speaking test without receiving any medication. Pretreatment with CBD significantly reduced anxiety, cognitive impairment, and discomfort in speech performance and significantly decreased alertness in their anticipatory speech. The placebo group displayed higher anxiety, cognitive impairment, discomfort, and alertness when compared with controls as assessed with the Visual Analogue Mood Scale (VAMS). The SSPS-N scores showed significant increases during testing of the placebo group that was almost abolished in the cannabidiol group. No significant differences were observed between the cannabidiol and control groups in SSPS-N scores or in cognitive impairment, discomfort, and alertness factors of the VAMS. The second part evaluated healthy subjects\' x y during a public speaking test following a high rimonabant oral dose, to understand better the possible pharmacological approaches for anxiety disorder treatment. Twenty four participants were randomly allocated to receive 0 or 90 mg rimonabant (n=12) in a double-blind design. No significant adverse effects were reported in either group. Participants who received rimonabant showed increased anxiety levels compared to placebo during anticipatory speech and performance measurements. Rimonabant treatment did not affect sedation, cognitive impairment, discomfort, blood pressure, heart rate, self-statements during public speaking, or bodily symptoms scales. Increased anxiety may reflect lower endocannabinoid activity in CB1 receptors and CB1 p \' possible role in modulation of anxiety and anxiety disorders. The third part aimed to monitor cannabinoid blood concentrations during sustained abstinence from chronic daily cannabis smoking. Thirty male chronic daily cannabis smokers resided on a secure clinical research unit for up to 33 days, with blood collected once daily. ?9-tetrahydrocannabinol (THC), 11-hydroxy-THC (11-OH-THC), and 11-nor-9-carboxy-THC (THCCOOH) whole blood concentrations were quantified by two-dimensional gas chromatography-mass spectrometry. Twenty-seven of 30 participants were THC-positive on admission, with a median (range) concentration 1.4 ng/mL (0.3-6.3). THC decreased gradually with only 1 of 11 participants negative at 26 days; 2 of 5 participants remained THC-positive (0.3 ng/mL) for 30 days. 5.0% f p p h TH >=1 0 g/ L f 12 y M 11-OH-THC w 1 1 g/ L w h >=1 0 g/ L 24h THCCOOH detection rates were 96.7 on admission, decreasing slowly to 95.7 and 85.7% on days 8 and 22, respectively; four of 5 participants remained THCCOOH positive (0.6-2.7 ng/mL) after 30 days and one remained positive on discharge at 33 days. THC was quantified in some participants for 30 days, albeit in low concentrations, due to the large cannabinoid body burden from extended exposure